International course of physical education (Fiep Bulletin - online, 2015)
This course was organized by the “INEF” (National Institute of Physical Education), at Cruz Quebrada – Lisbon And Patronized by the FIEP. It was directed by Prof. José Noronha Feio, Director of the Institute and FIEP’s Delegate in Portugal.